Feasible approaches and implementation challenges to atrial fibrillation screening: a qualitative study of stakeholder views in 11 European countries. Issue 6 (21st June 2022) - Engler, Daniel; Hanson, Coral L; Desteghe, Lien; Boriani, Giuseppe; Diederichsen, Søren Zöga; Freedman, Ben; Palà, Elena; Potpara, Tatjana S; Witt, Henning; Heidbuchel, Hein; Neubeck, Lis; Schnabel, Renate B
Abstract : Objectives: Atrial fibrillation (AF) screening may increase early detection and reduce complications of AF. European, Australian and World Heart Federation guidelines recommend opportunistic screening, despite a current lack of clear evidence supporting a net benefit for systematic screening. Where screening is implemented, the most appropriate approaches are unknown. We explored the views of European stakeholders about opportunities and challenges of implementing four AF screening scenarios. Design: Telephone-based semi-structured interviews with results reported using Consolidated criteria for Reporting Qualitative research guidelines. Data were thematically analysed using the framework approach. Setting: AF screening stakeholders in 11 European countries. Participants: Healthcare professionals and regulators (n=24) potentially involved in AF screening implementation. Intervention: Four AF screening scenarios: single time point opportunistic, opportunistic prolonged, systematic single time point/prolonged and patient-led screening. Primary outcome measures: Stakeholder views about the challenges and feasibility of implementing the screening scenarios in the respective national/regional healthcare system. Results: Three themes developed. (1) Current screening approaches: there are no national AF screening programmes, with most AF detected in symptomatic patients. Patient-led screening exists via personal devices, creating screening inequity. (2) Feasibility of screening: single time point opportunistic screening in primary care using single-lead ECG devices was considered the most feasible. Software algorithms may aid identification of suitable patients and telehealth services have potential to support diagnosis. (3) Implementation requirements: sufficient evidence of benefit is required. National screening processes are required due to different payment mechanisms and health service regulations. Concerns about data security, and inclusivity for those without primary care access or personal devices must be addressed. Conclusions: There is an overall awareness of AF screening. Opportunistic screening appears the most feasible across Europe. Challenges are health inequalities, identification of best target groups for screening, streamlined processes, the need for evidence of benefit and a tailored approach adapted to national realities.